Komunitas Fujoshi di Pontianak dan Stigma Identitas Gender yang Melekat dalam Lingkungan Masyarakat - Krismi Tariuni; Dahniar Th. Musa; Zakiah Hasan Gaffar (Balale' : Jurnal Antropologi, 2022)
The study examined The Fujoshi Community in Pontianak and the attached stigma of gender identity within the society. This fujoshi community is active on Whatsapp social media. They are a community of homoerotic lovers or boys love formed by people who also like boys love from various circles, both otaku, k-popers, and who just like boys love. There are some stigmas that are received to fujoshi because they enjoyed reading and watching homoerotic themed. The research implemented ethnographic research method with participants observation and online interviews to collect the data. The Social Construction Theory of Reality by Peter L. Berger is used in this research. The aim of the study was to describe fujoshi in Whatsapp groups to provide interpretations of homosexuals in reading and series boys love among heteronormative values and to describe fujoshi's means to maintain that identity and face the stigma as well as heteronormative values in society. The results showed that many factors drived fujoshi love boys love and the fans of boys love to form a community of fujoshi on Whatsapp to share information with fellow fans. The community was formed for fujoshi to express their passion for boys love in the midst of a heteronormative society.